2011
DOI: 10.1007/s00213-011-2402-5
|View full text |Cite
|
Sign up to set email alerts
|

Naloxone attenuation of ethanol-reinforced operant responding in infant rats in a re-exposure paradigm

Abstract: Self-administration of ethanol was established in terms of operant responding in preweanling rats with no previous exposure to the drug. Pairing of naloxone with ethanol, at a point separate in time from operant responding, reduced ethanol reinforcement. This indicated participation of the opioid system in ethanol reinforcement. This effect seems not to be unique to ethanol but also is observable when sucrose acts as reinforcer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 61 publications
4
29
0
Order By: Relevance
“…Therefore, data were collapsed across sex for all the remaining analyses. The absence of sex effects has also been observed in prior studies when employing a variety of reinforcers in operant conditioning tasks during early ontogeny (Bordner et al, 2008; March et al, 2009; Miranda-Morales et al, 2010, 2012a,b, 2014). …”
Section: Methodssupporting
confidence: 57%
“…Therefore, data were collapsed across sex for all the remaining analyses. The absence of sex effects has also been observed in prior studies when employing a variety of reinforcers in operant conditioning tasks during early ontogeny (Bordner et al, 2008; March et al, 2009; Miranda-Morales et al, 2010, 2012a,b, 2014). …”
Section: Methodssupporting
confidence: 57%
“…In the preclinical literature the use of operant techniques to evaluate the motivational effects of ethanol during early ontogeny has been recently documented in the literature (Bordner, Molina, & Spear, 2008; March, Abate, Spear, & Molina, 2009; Miranda-Morales, Molina, Spear, & Abate, 2010, 2012a; Miranda-Morales, Spear, Nizhnikov, Molina, & Abate, 2012b; Ponce, Pautassi, Spear, & Molina, 2008). In 1-day-old rats, ethanol's sensorial properties were sufficient to promote vigorous operant responses when ethanol ingestion was contingent upon operant behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies showed that this sensitivity to ethanol reinforcement during early ontogeny can also be observed during the second postnatal week of the infant rat. For instance, self-administration of ethanol was established in terms of operant responding in preweanling rats with no previous exposure to the drug (Miranda-Morales, Molina, et al, 2012a; Miranda-Morales, Spear, et al, 2012b; Ponce et al, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, data were collapsed across sex for all of the subsequent analyses. The lack of sex effects was not unexpected: previous studies working with ethanol-related effects in rats of the present age (Arias & Chotro, 2005; Chotro & Arias, 2003; Miranda-Morales, Molina, et al, 2012; Miranda-Morales, Spear, et al, 2012) usually have found no significant effects of gender or interaction with other factors.…”
Section: General Methodsmentioning
confidence: 52%
“…On PD 13, infants were separated from their dams, cannulated, and placed in pairs in a holding cage (45 × 20 × 20 cm). Intraoral cannulation was performed using a procedure extensively described in previous studies (Chotro & Arias, 2003; Miranda-Morales, Molina, Spear, & Abate, 2012; Miranda-Morales, Spear, Nizhnikov, Molina, & Abate, 2012; Spear, Specht, Kirstein, & Kuhn, 1989). The entire procedure took less than 5 sec per pup.…”
Section: General Methodsmentioning
confidence: 99%